Association of N-Methyl-D-Aspartate receptor 2B Subunit (GRIN2B) polymorphism with earlier age at onset of withdrawal symptoms in Indian alcohol dependent subjects. Issue 1 (2nd January 2017) - Paul, Pradip; Dahale, Ajit; Kishore, Brij; Chand, Prabhat; Benegal, Vivek; Jain, Sanjeev; Murthy, Pratima; Purushottam, Meera
ABSTRACT: The associations of GRIN2B polymorphism (rs1806201) with alcohol withdrawal and related clinical parameters in alcohol dependent subjects were investigated. Cases were assessed using a semi-structured clinical pro forma for alcohol abuse and a questionnaire for family history of alcohol dependence and psychiatric disorders after obtaining informed consent. The study included alcohol dependent male cases ( n = 220, age at onset of alcohol withdrawal symptoms = 32.4 ± 8.8 y ) recruited at the Center for Addiction Medicine, National Institute of Mental Health and Neurosciences, Bangalore, India. The controls comprised of healthy unrelated males ( n = 183) who were ethnically matched and selected randomly. The polymorphism rs1806201 was analyzed by polymerase chain reaction and restriction fragment length polymorphism. The presence of T allele at this locus was significantly associated with lower age at onset of alcohol withdrawal symptoms ( p = .005) among the cases. Mean age at onset of alcohol withdrawal symptoms in subjects who were T carriers was 31.4 ± 8.5 y ( n = 160) and non-T carriers was 35.2 ± 9.0 y ( n = 60). The SNP rs1806201 in GRIN2B may play an important role in genetic susceptibility to earlier age of withdrawal in alcohol dependent patients.